THE SPECIFICITY AND COMPLEXITY OF THE PROCESS OF LEARNING ENGLISH - Khodjayev K. K. (Research Parks Publishing LLC, 2021)
This article discusses the specificity and complexity of the process of learning English. Methodological assistance and recommendations were provided to English language learners.